2002
DOI: 10.1303/aez.2002.285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of synthesized tannin on the growth and survival of a generalist herbivorous insect, the common cutworm, Spodoptera litura Fabricius (Lepidoptera: Noctuidae).

Abstract: We examined the effects of tannin on a generalist herbivorous insect, the common cutworm (Spodoptera litura). The dosage effect was estimated by measuring the growth performance of the cutworm when the larvae were fed artificial diets containing different amounts of synthesized tannin. We used artificial diets to exclude the effects of non-tannin defense mechanisms in plant foliage. Indices of growth performance, number of dead larvae, pupal weight, total feeding amount and length of larval period were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 29 publications
0
24
0
1
Order By: Relevance
“…The prolongation of the larval stage of insects caused by the ingestion of natural products has been reported in the literature. Nomura and Itioka (2002) observed an increase in the duration of larval and pupal stages, as well as in larval mortality, and a reduction of adult emergence from the application of synthetic tannins on artificial diets of Spodoptera litura (Fabricius, 1775) (Lepidoptera: Noctuidae), and found that the reduction in larval growth was proportional to the concentration of the substance ingested.…”
Section: Resultsmentioning
confidence: 99%
“…The prolongation of the larval stage of insects caused by the ingestion of natural products has been reported in the literature. Nomura and Itioka (2002) observed an increase in the duration of larval and pupal stages, as well as in larval mortality, and a reduction of adult emergence from the application of synthetic tannins on artificial diets of Spodoptera litura (Fabricius, 1775) (Lepidoptera: Noctuidae), and found that the reduction in larval growth was proportional to the concentration of the substance ingested.…”
Section: Resultsmentioning
confidence: 99%
“…A presença de taninos é evidência da atividade antialimentar contra insetos. Assim, Nomura & Itioka (2002) A fração proveniente de P. dubium prolongou a duração das fases larval e pupal de S. frugiperda, além de causar redução no peso e na percentagem de sobrevivência desse inseto na fase pupal (Tabela 3). O alongamento da fase larval observado para as lagartas tratadas com P. dubium possivelmente se deu em função da redução na ingestão de alimentos; assim foi necessário que essas lagartas permanecessem se alimentando por um maior período de tempo antes de atingirem a fase de pupa.…”
Section: Resultsunclassified
“…They are present in high contents (frequently between 5-40% dry weight) (Meyer andKarasov 1989, Adams et al 2009) and thus represent a high initial investment cost (Coley et al 1985). Their effects are the result of the tissue content (Feeny 1992, Nomura andItioka 2002), acting mainly by reducing digestibility rather than through direct toxicity (Bernays 1991, Eichhorn et al 2007). They are effective against a broad herbivore spectrum including specialist herbivores (Beck and Schoonhoven 1980, Coley et al 1985, Bernays and Chapman 1994.…”
Section: Introductionmentioning
confidence: 99%